Perception of Modern Processing Technology by Shea Butter Processors in Kwara State, Nigeria - Alaba Oluwakemi Akinsokeji; Ayanfunke Sarafat Tijani; Kabiru Mohammed Sanusi; Lucky Igene; Olusegun Martins Orifah (Journal of Agricultural Extension, 2017)
Abstract